Kantian and Anti-Kantian Philosophy of Language - Igor A. Mikhailov (Кантовский сборник)
This paper examines two models of language philosophy. The first is the Kantian philosophy which sees language as an instrument of conveying mental content. I have selected Immanuel Kant and Edmund Husserl from amongst its numerous representatives. In this tradition, a language expression, i.e. an expression that has meaning, is determined by the objectively ideal character of the meanings (“rules”) given through the subject’s intellectual acts. The main task is to fix with a maximum degree of accuracy what is “seen” in consciousness. This model inevitably considers words to be “markers” or “labels” which have no intrinsic power. The problem with this approach is, first, that it is impossible to determine the criteria by which this or that word should be considered adequate. Second, this approach leads to the creation of ever new philosophical languages which simultaneously challenge the tradition and yet claim to be a renewed version of it. It is shown that the fairly systematic critique of the Kantian approach by Johann Georg Hamann and Johann Gottfried Herder falls short of proposing an alternative philosophical system because, having a religious foundation, it does not offer a complete grounding of knowledge. In the wide range of anti-Kantian positions on the nature of language Gustav Shpet’s concept of language is singled out. It pursues the same task of creating a universal system of knowledge as Husserl’s phenomenology, but it proceeds from fundamentally different notions of philosophical knowledge. Unlike Husserl, whose thought is marked by revolutionary radicalism, for Shpet ideal knowledge is “positive”, “concrete”, “full” and “dynamic”. He considers philosophising to be dialectical and inherently dialogic. The result of philosophy meeting these ideals is the concept that our knowledge is centred on language and our experience has a sign-verbal character.